PENERAPAN SISTEM SOFT BIKAMERAL DALAM PARLEMEN DI INDONESIA - Taufik Hidayat; Dodi Haryono; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Legislative power which is also commonly referred to as the parliament is the principal institution in the country. Parliament has a significant role in the development and progress of a country. In general, the structure of the parliament in the world divided into two parliamentary two rooms and one room. Changes in the structure of Indonesian parliament after amendments to the Constitution of the Republic of Indonesia of the two-room system using a soft (soft bicameral). With the use of soft bicameral system then one of the rooms are deliberately limited constitutional authority. The implications of the application of soft bicameral system resulted in DPD performance experienced inefficiency until no significant impact on results (output) of the current parliamentary system ini.Purpose of this thesis, namely; First, the application of soft bicameral system in the Indonesian parliament, Second, improvement of soft bicameral system in the Indonesian parliament.This research is normative, which is done with the approach to find the law for a case in concerto, namely the approach of looking for how to find the relevant facts, then find the law in abstracto the right to object under study. Data sources used include primary data, secondary data, and the data tertiary. Data collection techniques using literature studies.From the research problem there are two main things that can be inferred. The first preliminary design DPD is not formed based on the context of checks and balances between the rooms in the parliamentary system (just as the subordination of parliament) so that the parliament has become lame, no institution but not functioned optimally,. Second, the problem lies in the constitution it is necessary to change the constitution by perfecting the current parliamentary system from soft to strong bicameral bicameral. Suggestions writer, First, improvements pattern DPR and DPD relationship should be mutually reinforcing regional interests accommodated maximum order, through product quality legislation will lead to the advancement of the nation, second, through changes to the constitution to encourage efforts to improve the system in the direction of strong bicameral parliament.Keywords: Parliament - Soft bicameral - strong bicameral